DEVELOPING ORAL SPEECH SKILLS THROUGH LISTENING TO PODCASTS (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
In today’s fast-paced digital age, language learners have a wealth of resources at their disposal, with podcasts becoming a particularly powerful tool for improving oral speech skills. Podcasts offer an engaging and accessible way for learners to enhance their language proficiency, especially in areas such as listening comprehension, pronunciation, vocabulary acquisition, and fluency.